AMMI analysis of cassava response to contrasting environments: case study of genotype by environment effect on pests and diseases, root yield, and carotenoids content in Cameroon - Hanna, R.; Kulakow, Peter A.; Parkes, Elizabeth Y.; Iluebbey, Peter O.; Ngome, F.A.; Suh, C.; Massussi, J.; Choutnji, I.; Wirnkar, V.L. (Springer, 2018)
Genotype by environment interaction remains a substantial issue in all breeding programs. Crop genotypes are generally developed in a central breeding location, but always require the evaluation of breeding products in different environments. This is particularly relevant in countries that have a wide range of climates. Eighteen cassava genotypes were evaluated in Cameroon in eight environments—varying in seasonal rainfall and temperature patterns and soil characteristics—over two cropping seasons. Soil nutrient content was analyzed and trials were established in a randomized complete block design in three replications. Response of genotypes to major cassava pests and diseases, yield and carotenoids content was evaluated. It was observed that four genotypes did not show cassava mosaic disease (CMD) symptoms irrespective of the environments. The local check had highest CMD incidence and severity across all environments. Average number of whitefly per plant across all environments was highest on TMS 96/0023. Average cassava green mite (CGM) infestation was low on all the genotypes. Fresh root yield of five genotypes ranged between 25 and 30 tons per ha for both years. Significant and positive correlation was found across locations between fresh root yield and soil K, P and Mg. AMMI analysis revealed highly significant differences among genotypes and environments and significant genotype × environment interaction for most of the estimated traits, indicating variability in genotypes performance with environment.